Rendimientos productivos de forraje verde hidropónico en dos variedades de maíz (Zea maiz) criollo blanco y amarillo en la parroquia Calderón, Quito. - Avila Villalta, Dario Xavier (2023)
The growth of the world's population has inadvertently led to an increase in the demand for food and other basic resources. In addition, the growing social and political interest in the adoption of more sustainable and circular food production systems. For efficient food production, alternative production systems are needed. One solution is to resort to hydroponic agriculture. In this context, the research on Productive Yields of Hydroponic Green Forage in two Varieties of Maize (Zea maiz) white and yellow creole was carried out in the Calderón parish, Quito canton, Pichincha province; which had as objectives, to determine the productive parameters of two varieties of yellow and white creole corn in the production of hydroponic green forage; and, the cost of production of the two varieties of yellow and white creole corn, and socialize the results of the research. The design used was experimental because two varieties of maize were used, one treatment for each variety with three repetitions for each treatment, in which weight and length were considered as variables. The results showed 1 kg of seed as a starting point where a production of 7 kg of white maize hydroponic green forage was achieved, being the treatment with the highest weight obtained from this variety, likewise the maximum final length obtained is 20.7 cm in T1R1, resulting in this treatment as the one with the highest growth. In relation to costs, these did not present differences, however, white corn presented better performance both in weight and final length, which shows that it is a better option for the production of HGF. Keywords: Growth, treatment, cost, length, weight.